2015
DOI: 10.1007/s10620-015-3595-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Treatment Outcomes of Cryptogenic Multifocal Ulcerous Stenosing Enteritis in Korea

Abstract: CMUSE is difficult to diagnose and is an easily relapsing disease. Female patients might have a better prognosis than male patients in terms of the relapse-free time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 19 publications
3
48
1
1
Order By: Relevance
“…Systemic corticosteroids may help but most patients develop corticosteroid dependent (1). Chung et al (2) found a response rate of corticosteroid was approximately 25%. To be able to wean corticosteroid, we attempted to use azathioprine as a maintenance immunomodulator that is frequently used in IBD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Systemic corticosteroids may help but most patients develop corticosteroid dependent (1). Chung et al (2) found a response rate of corticosteroid was approximately 25%. To be able to wean corticosteroid, we attempted to use azathioprine as a maintenance immunomodulator that is frequently used in IBD.…”
Section: Discussionmentioning
confidence: 97%
“…Cryptogenic multifocal ulcerous stenosing enteritis is a rare idiopathic cause of ulceration and stricture of small bowel, which can be presented with acute or chronic GI bleeding, symptoms of bowel obstruction, abdominal pain, anemia, hypoalbuminemia, and perforation (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Digestive Diseases and Sciences [1], Chung and colleagues from South Korea describe a multicenter case series of ''cryptogenic multifocal ulcerous stenosing enteritis'' or CMUSE, defined using modern endoscopic methods for small intestinal mucosal evaluation and followed up for an extended period. Through these observations, the authors provide novel information regarding the long-term natural history of CMUSE, a specific syndrome initially described more than a half-century ago largely, although not entirely, in the French literature [2][3][4][5][6].…”
Section: Background and Significancementioning
confidence: 99%
“…At present, CMUSE is diagnosed mainly based on clinical and macroscopic imaging features of the small intestine. However, CMUSE is frequently misdiagnosed as other ulcerative small bowel diseases, such as Crohn’s disease (CD) or nonsteroidal anti-inflammatory drugs (NSAIDs)-induced enteropathy, because of similar clinical symptoms and nonspecific laboratory findings[3,4]. …”
Section: Introductionmentioning
confidence: 99%